1995
DOI: 10.1103/physrevb.51.8564
|View full text |Cite
|
Sign up to set email alerts
|

Correlated local distortions of the TlO layers inTl2Ba2

Abstract: We have used the XAFS (x-ray-absorption fine structure) technique to investigate the local structure about the Cu, Ba, and Tl atoms in orthorhombic T12BaqCuO"with a superconducting transition temperature T, =60 K. Our results clearly show that the 0(1), 0(2), Cu, and Ba atoms are at their ideal sites as given by the diffraction measurements, while the Tl and 0(3) atoms are more disordered than suggested by the average crystal structure. The Tl-Tl distance at 3.5 A, between the T10 layers does not change, but t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
(168 reference statements)
0
11
0
Order By: Relevance
“…In the thallium-based superconductors, short range correlated Tl and O ordering in the Tl-O planes have been proposed in the Tl 2 Ba 2 CuO 6−δ (Tl2201) 24,25 and Tl 2 Ba 2 CaCu 2 O 8−δ (Tl2212) 26 materials. Ultrasonic method may provide further insight into the nature of the ordering process and the superconductivity in the Tl-based cuprates.…”
Section: Introductionmentioning
confidence: 99%
“…In the thallium-based superconductors, short range correlated Tl and O ordering in the Tl-O planes have been proposed in the Tl 2 Ba 2 CuO 6−δ (Tl2201) 24,25 and Tl 2 Ba 2 CaCu 2 O 8−δ (Tl2212) 26 materials. Ultrasonic method may provide further insight into the nature of the ordering process and the superconductivity in the Tl-based cuprates.…”
Section: Introductionmentioning
confidence: 99%
“…Thus for instance, in YBCO, the chain ordering splits the degeneracy of the X and Y point VHS's. In Tl-1201 and Tl-1212, the structural distortions have been analyzed in detail [613]. The O-atoms show a very large displacement from their nominal positions, and this distortion breaks the symmetry of the two in-(CuO 2 -)plane O's, thereby lifting the VHS degeneracy.…”
Section: Vhs Relatedmentioning
confidence: 99%
“…Here we briefly describe our study of the Tl layer region; a more detailed discussion is found in Ref. [5].…”
Section: Distortions In the Tl Layer In Tl 2201mentioning
confidence: 99%